Amphibia, Anura, Cycloramphidae, Proceratophrys moratoi (Jim and Caramaschi, 1980): Distribution extension and new altitudinal record in state of São Paulo, Brazil - Rolim, Daniel Contieri [UNESP]; Martinez, Rosangela Aparecida Marques; de Almeida, Silvio César [UNESP]; Ubaid, Flávio Kulaif [UNESP]; Maffei, Fábio [UNESP]; Jim, Jorge [UNESP] (Pensoft Publishers, 2010)
Here we present a new record of the little toad Proceratophrys moratoi for the state of São Paulo, in the municipality of Bauru. This record extends to the known distribution of P. moratoi around 80 km northwestern from its type locality and around 115 km west from other known populations of this species. It also corresponds to the lowest elevation where the species has been found, approximately 200 m altitude below the known records. © 2010 Check List and Authors.